Acceptability of COVID-19 Vaccination among Health Care Workers in Ghana. (20th April 2021) - Agyekum, Martin Wiredu; Afrifa-Anane, Grace Frempong; Kyei-Arthur, Frank; Addo, Bright
Abstract : Because health care workers are a reliable source of health information, their acceptance or rejection of COVID-19 vaccines can influence the general population's uptake of COVID-19 vaccines. In this study, we sought to determine the acceptability of COVID-19 vaccines among health care workers in Ghana. Using a cross-sectional design, we collected data from 234 health care workers through a self-administered online survey from 16 January to 15 February 2021. Descriptive, bivariate, and multivariate analyses were performed using STATA version 15. The findings revealed that 39.3% ( n  = 92) of health care workers intended to receive the COVID-19 vaccines. Factors such as sex (AOR = 0.451; CI 95% 0.240–0.845; p = 0.013 ), category of health care workers (AOR = 2.851; 95 CI%: 1.097–7.405; p = 0.031 ), relative being diagnosed with COVID-19 (AOR = 0.369; CI 95% 0.145–0.941; p = 0.037 ), and trust in the accuracy of the measures taken by the government in the fight against COVID-19 (AOR = 2.768; CI 95%: 1.365–5.616; p = 0.005 ) proved to be significant predictors of the acceptability of the COVID-19 vaccine. Concerns about the safety of vaccines ( n  = 93, 65.5%) and the adverse side effects of the vaccines ( n  = 23, 14.8%) were identified as the main reasons why health care workers would decline uptake of COVID-19 vaccines in Ghana. The self-reported low intention of health care workers in Ghana to accept COVID-19 vaccines necessitates an urgent call from the Government of Ghana and other stakeholders to address health care workers' concerns about the safety and adverse side effects of COVID-19 vaccines, as this would increase vaccine uptake. Interventions must also take into consideration sex and the category of health care workers to achieve the desired results.